Pengaruh Kemudahan, Keamanan dan Kecepatan Transaksi Terhadap Keputusan Konsumen pada Pengguna QRIS di Denpasar Selatan - Febianti Yulia Putri; Ni Ketut Anjani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The development of digital technology has driven changes in people's transaction behavior, including the increasing use of non-cash payment systems such as the Quick Response Code Indonesian Standard (QRIS). This study aims to analyze the influence of convenience, security, and transaction speed on consumer decisions to use QRIS in South Denpasar. This study used a quantitative approach with a survey method by distributing questionnaires to 170 QRIS user respondents in South Denpasar who were selected using a purposive sampling technique. Data were analyzed using multiple linear regression with the help of SPSS. The results showed that partially convenience, security, and transaction speed had a positive and significant effect on consumer decisions. Simultaneously, these three independent variables also had a significant effect on consumer decisions to use QRIS. This finding indicates that the easier, safer, and faster the transaction process using QRIS, the higher the consumer's decision to use it for payment activities. This study is expected to provide input for related parties in improving the quality of QRIS services, especially in terms of ease of use, system security, and transaction speed to encourage increased QRIS use in the community.